Proposed Development Models of Islamic Movements in Post Reformation Indonesia - Gonda Yumitro; Elfatih Abdullahi Abdelsalam; Syaza Farhana Mohamad Shukri (IAIN Ponorogo, 2020)
Abstract: This article tries to analyze the models of Islamic movements in post-reformation Indonesia. The major research problem posed is to highlight the main theoretical underpinnings of the momentum of reformation and its impact on various movements, particularly the Islamic ones. The focus here is to explain how these Islamic movements have developed strategies and models to face and circumvent the challenges. This is qualitative research that used documentary analysis and the Focused Group Discussion (FGD) in collecting information and data for analysis. In analyzing the data, the authors used Nvivo 12 Plus. This research found that the Islamic movements of Indonesia, in their quest for development and influence, have availed themselves of several developmental models, such as transnational and national Islamic movements, political and non-political movements, democratic and anti-democratic, and moderate and radical Islamic movements.المللخص: تحلّل هذه المقالة نماذج الحركات الإسلامية في إندونيسيا بعد الإصلاح. تتمثل المشكلة الرئيسية للبحث التي أثيرت في إبراز النظري الأساسي لزخم الإصلاح وتأثيره على الحركات المختلفة، وخاصة الحركة الإسلامية. ينصب التركيز هنا على شرح كيفية قيام هذه الحركات الإسلامية بتطوير استراتيجيات ونماذج لمواجهة التحديات التي تواجهها وحلها. هذا البحث هو بحث نوعي يستخدم أساليب التحليل الوثائقي والمناقشة الجماعية المركزة (ف.غ.د) في جمع المعلومات وتحليل البيانات. في تحليل البيانات، يستخدم الباحث ن.فيفو 12 بلس. تتمثل النتائج الرئيسية لهذا البحث في أن الحركة الإسلامية في إندونيسيا استجابة للدستور الحالي قد تطورت إلى عدة نماذج، مثل الحركات الإسلامية عبر الوطنية والوطنية، والحركات السياسية وغير السياسية، والديمقراطية ومناهضة الديمقراطية، وكذلك الحركات الإسلامية المعتدلة والمتطرّفة.Abstrak: Artikel ini menganalisis model gerakan Islam pasca reformasi di Indonesia. Permasalahan utama penelitian yang dikemukakan adalah menyoroti landasan teori utama momentum reformasi dan dampaknya terhadap berbagai gerakan khususnya gerakan Islam. Fokus di sini adalah menjelaskan bagaimana gerakan-gerakan Islam tersebut mengembangkan strategi dan model untuk menghadapi dan menyelesaikan tantangan mereka hadapi. Penelitian ini merupakan penelitian kualitatif yang menggunakan metode documentary analysis dan Focused Group Discussion (FGD) dalam pengumpulan informasi dan analisis data. Dalam menganalisis data, penulis menggunakan Nvivo 12 Plus. Temuan utama dari penelitian ini adalah bahwa gerakan Islam di Indonesia dalam merespon konstilasi yang ada telah berkembang menjadi beberapa model, seperti gerakan Islam transnasional dan nasional, gerakan politik dan non-politik, demokrasi dan anti-demokrasi, serta gerakan Islam moderat dan radikal.